A kind of anti-dendrite high-reliability solder paste and preparation method thereof
By introducing anti-dendrite high-reliability solder paste composed of SnAgCuBi alloy powder and specific flux into the solder paste, the dendrite growth and defect problems during the solder paste are solved, and the high performance and reliability of the solder joint are achieved.
Patent Information
- Application Number
- CN202510083537.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Traditional solder paste is prone to dendrite growth problems during the welding process, resulting in a decrease in the performance of the solder joints and defects such as pores and slag inclusions, which affects the reliability and service life of electronic products.
An anti-dendrite high-reliability solder paste is used, and its composition includes 85-88 parts of SnAgCuBi alloy powder and 12-15 parts of flux. The flux is composed of a compound rosin, a compound resin, an activator, a thixotropic agent and an antioxidant. Through the combination of these components, the solid-liquid interface stability and rheological characteristics during the welding process are improved.
Effectively inhibit dendrites' growth, improve the mechanical and electrical properties of welding joints, reduce welding defects, and improve the reliability and service life of electronic products.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the field of soldering materials, and in particular relates to an anti-dendrite high-reliability solder paste and a preparation method thereof. Background Art
[0002] Solder paste is an important industrial raw material for connecting electronic components in welding circuits and is widely used in the electronics manufacturing industry. With the continuous miniaturization and precision of electronic products, the performance requirements for solder paste are getting higher and higher. Traditional solder paste is prone to dendrite growth during the welding process, which will cause the performance of the welded joint to deteriorate and even cause welding failure.
[0003] Dendrite growth is a phenomenon in which the solid-liquid interface becomes unstable due to solute redistribution and interfacial energy during the solidification process of solder paste, thus forming dendrites. Dendrite growth not only affects the microstructure of the solder joint, but also reduces the mechanical and electrical properties of the joint, thus affecting the reliability and service life of electronic products.
[0004] In addition, conventional solder paste may produce defects such as pores and slag inclusions during the soldering process, which can also reduce the performance of the solder joint. Therefore, it is particularly important to develop a solder paste that can improve anti-dendrite capability and has high reliability.
[0005] At present, although there are some anti-dendrite solder pastes on the market, these solder pastes still have some deficiencies in performance. For example, some solder pastes have poor anti-dendrite effect and cannot effectively inhibit the growth of dendrites; while other solder pastes have certain anti-dendrite capabilities, but perform poorly in other properties.
[0006] Therefore, it is necessary to develop a new type of solder paste, which not only has excellent anti-dendrite ability, but also can maintain good comprehensive properties such as welding strength, so as to meet the demand of modern electronic manufacturing industry for high-performance solder paste. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a solder paste having excellent anti-dendrite capability and capable of maintaining good comprehensive properties such as welding strength, so as to meet the demand for high-performance solder paste in the modern electronic manufacturing industry.
[0008] To achieve the above object, the present invention discloses the following technical solutions:
[0009] In a first aspect, the present invention provides a high-reliability anti-dendrite solder paste, which comprises the following components by weight: 85-88 parts of solder alloy powder and 12-15 parts of flux;
[0010] The solder alloy powder is SnAgCuBi alloy powder;
[0011] The soldering flux is composed of the following components in percentage by mass:
[0012] Compound rosin 27-35%;
[0013] Compound resin 13-15%;
[0014] Activator 4-8%;
[0015] Thixotropic agent 2-3%;
[0016] Antioxidants 0.7-1%;
[0017] Solvent residue;
[0018] The compound rosin is composed of water-white hydrogenated rosin, acrylic rosin and light-colored rosin;
[0019] The activator is composed of myristic acid, 4-hydroxyphenylpyruvic acid and triethanolamine tris(dihydrogen phosphite) sodium salt;
[0020] The thixotropic agent consists of polyamide-modified hydrogenated castor oil, ethylenebismyristic acid amide and polyethylene wax.
[0021] Preferably, the solder alloy powder consists of the following components in percentage by mass:
[0022] Ag 2.5-3.5%;
[0023] Cu 0.5-1%;
[0024] Bi 0.05-0.1%;
[0025] The balance is Sn and inevitable impurities.
[0026] Preferably, the mass ratio of water-white hydrogenated rosin, acrylic rosin and light-colored rosin in the compound rosin is (2-3):1:(1-2).
[0027] Preferably, the compound resin is a compound of at least two of polyethylene, polypropylene and polycarbonate.
[0028] Preferably, the mass ratio of myristic acid, 4-hydroxyphenylpyruvic acid and triethanolamine tris(dihydrogen phosphite) sodium salt in the activator is 4:(0.3-0.5):(1.4-2.1).
[0029] Preferably, the mass ratio of polyamide-modified hydrogenated castor oil, ethylene bismyristamide and polyethylene wax in the thixotropic agent is 1:(1.1-1.4):(1.8-2.2).
[0030] Preferably, the antioxidant is at least one of methylbenzotriazole, 2-methylimidazole and benzimidazole.
[0031] Preferably, the solvent is a mixture of triethylene glycol butyl ether and diethylene glycol monooctyl ether in a mass ratio of (2-3):1.
[0032] In a second aspect, the present invention provides a method for preparing the above-mentioned anti-dendrite high-reliability solder paste, comprising the following steps:
[0033] (1) Weigh each component according to the formula and set aside;
[0034] (2) Add the solvent into the container, heat to 110-130°C and keep warm, add the compound rosin, stir until the compound rosin is completely dissolved, continue to add the compound resin, stir and mix evenly, and obtain mixture A;
[0035] (3) Lowering the temperature of mixture A to 70-80°C and then keeping it warm, adding a thixotropic agent, an activator and an antioxidant, and stirring for 20-30 minutes to obtain a soldering flux;
[0036] (4) Add the flux obtained in step (3) and the solder alloy powder into a solder paste mixer, mix and stir for 30-60 minutes to obtain the anti-dendrite high-reliability solder paste;
[0037] The particle size of the solder alloy powder is ≤40 μm, and the content of the solder alloy powder with a particle size of 20-38 μm is 90 wt% or more.
[0038] Furthermore, the stirring speed in step (3) is 300-500 r / min; and the mixing and stirring speed in step (4) is 30 r / min.
[0039] In the present invention:
[0040] The activator composed of myristic acid, 4-hydroxyphenylpyruvic acid and triethanolamine tri(dihydrogen phosphite) sodium salt acts in the welding process to improve the wettability of the solder by removing oxides on the metal surface, reduce surface tension, and thus improve the welding effect. The activator provided by the present invention also helps to reduce welding defects, such as the balling phenomenon of solder joints caused by poor wetting, and prevents metal re-oxidation during the welding process, protects the welding area from further oxidation and corrosion, and ensures the reliability and performance of welding. The activator provided by the present invention decomposes after high-temperature welding, has no acidic residue after welding, has a low risk of ion migration, has high insulation impedance, does not produce corrosive electromigration, and does not cause the risk of short circuit of fine-pitch solder joints.
[0041] The role of thixotropic agent in solder paste is to adjust the rheological properties of solder paste so that it maintains appropriate viscosity when static to prevent sedimentation or stratification, and provides good fluidity during printing to facilitate accurate printing. The thixotropic agent composed of polyamide-modified hydrogenated castor oil, ethylene bismyristamide, and polyethylene wax enhances the shear resistance of solder paste, reduces collapse and glue overflow during printing, and improves printing accuracy. At the same time, it prevents ion migration, has high insulation impedance, does not produce corrosive electromigration, reduces dendrite growth, and thus reduces the risk of short circuits in fine-pitch solder joints, improves welding reliability, ensures a smooth welding process, and improves the final welding quality.
[0042] Beneficial effects of the present invention:
[0043] 1. The thixotropic agent provided by the present invention has extremely high stability, can prevent ion migration, has high insulation impedance, does not produce corrosive electromigration, reduces dendrite growth, and thus reduces the risk of short circuits in fine-pitch solder joints;
[0044] 2. The activator provided by the present invention can achieve decomposition after high-temperature welding, has low acid residue after welding, low risk of ion migration, high insulation impedance, no corrosive electromigration, reduces dendrite growth, and thus reduces the risk of short circuit in fine-pitch solder joints. DETAILED DESCRIPTION
[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0046] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the invention.
[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0049] The technical solution of the present invention is further described in detail below in conjunction with embodiments.
[0050] In the present invention:
[0051] Water-white hydrogenated rosin: Guangxi Wuzhou Richeng Forest Products Chemical Co., Ltd.;
[0052] Acrylic rosin: Arakawa Chemical Industries, Ltd., Japan;
[0053] Light-colored rosin: Guangxi Wuzhou Richeng Forest Products Chemical Co., Ltd.
[0054] Hydrogenated rosin: Arakawa Chemical Industries, Ltd., Japan;
[0055] Polyamide modified hydrogenated castor oil: Shenzhen Xinzhihe New Materials Co., Ltd.;
[0056] Ethylene bis-myristamide: Shenzhen Xinzhihe New Materials Co., Ltd.;
[0057] Polyethylene wax: Shenzhen Xinzhihe New Materials Co., Ltd.
[0058] Hydrogenated castor oil: Shenzhen Jintenglong Industrial Co., Ltd.;
[0059] Other raw materials are commercially available.
[0060] Preparation of flux
[0061] The compounded rosin is compounded according to the mass ratio of the raw materials in Table 1:
[0062] Table 1. Ratio of compound rosin raw materials
[0063] raw material Compound rosin 1 Compound rosin 2 Compound rosin 3 Compound rosin 4 Compound rosin 5 Compound rosin 6 Compound rosin 7 Compound rosin 8 Compound rosin 9 Water White Hydrogenated Rosin 2 2.5 3 - 3.125 3.57 - 5 - Acrylic rosin 1 1 1 2 - 1.43 1 - - Light rosin 1 1.5 2 3 1.875 - 1.5 - 5 Hydrogenated rosin - - - - - - 2.5 - -
[0064] Note: “-” in the table means not added.
[0065] The activator is compounded according to the mass ratio of the raw materials in Table 2:
[0066] Table 2 Activator raw material mass ratio
[0067] Activator 1 Activator 2 Activator 3 Activator 4 Activator 5 Activator 6 Activator 7 Activator 8 Active Agent 9 Myristic acid 4 4 4 - 4 4 1 2 - 4-Hydroxyphenylpyruvic acid 0.3 0.4 0.5 0.4 - 0.4 1 1 - Triethanolamine tris(dihydrogen phosphite) sodium salt 1.4 1.7 2.1 1.7 1.7 - 1 2 - Palmitic acid - - - 4 - - - - 2.71 2-Oxovaleric acid - - - - 0.4 - - - 0.85 Triethanolamine - - - - - 1.7 - - 2.54
[0068] Note: “-” in the table means not added.
[0069] The thixotropic agent is compounded according to the mass ratio of the raw materials in Table 3:
[0070] Table 3 Thixotropic agent raw material mass ratio
[0071] Thixotropic agent 1 Thixotropic agent 2 Thixotropic agent 3 Thixotropic agent 4 Thixotropic agent 5 Thixotropic agent 6 Polyamide modified hydrogenated castor oil 1 1 1 - 1 1 Ethylene bismyristamide 1.1 1.3 1.4 1.3 1 1 Polyethylene wax 1.8 2.0 2.2 2.0 2 1 Hydrogenated castor oil - - - 1 - -
[0072] Note: “-” in the table means not added.
[0073] The flux is prepared according to the mass percentage of the raw materials in Table 4:
[0074] Table 4 Mass percentage of flux raw materials
[0075]
[0076] Note: “-” in the table means not added.
[0077] The preparation of the soldering flux comprises the following steps:
[0078] Step (1), weigh each component according to the raw material formula in Table 4 and set aside;
[0079] Step (2), adding the solvent into a container, heating to 130°C and then keeping the temperature, adding the compounded rosin, stirring until the compounded rosin is completely dissolved, and continuing to add the compounded resin, stirring and mixing evenly to obtain a mixture A;
[0080] Step (3), reducing the temperature of the mixture A to 80° C. and then keeping the temperature, adding a thixotropic agent, an activator and an antioxidant, and stirring at a rotation speed of 400 r / min for 30 minutes to obtain a soldering flux.
[0081] Preparation of solder paste
[0082] The raw materials are weighed according to the ratio in Table 5, and the flux obtained in the above step (3) and the solder alloy powder are added into a solder paste mixer at a temperature of 25±3°C, and mixed and stirred for 30-60 minutes at a speed of 30 r / min to obtain the anti-dendrite high-reliability solder paste; wherein the solder alloy powder is smelted from 95.4% Sn, 3.5% Ag, 0.1% Bi and 1% Cu, the particle size of the solder alloy powder is ≤40 μm, the particle size is 20-38 μm, and the content is 90wt% or more.
[0083] Table 5 Solder paste raw material quality ratio
[0084] raw material Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 Comparative Example 12 Comparative Example 13 Comparative Example 14 Comparative Example 15 Solder Alloy Powder 85 87 88 87 87 87 87 87 87 87 87 87 87 87 87 87 87 87 Flux 15 13 12 13 13 13 13 13 13 13 13 13 13 13 13 13 13 13 Flux serial number 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18
[0085] Performance Testing
[0086] 1. Evaluation of oxide residue after welding
[0087] Residue: The test base material is a copper substrate of 30 mm × 30 mm × 0.1 mm. The solder pastes prepared in Examples 1-3 and Comparative Examples 1-14 are coated on the base material in equal amounts. The soldering is performed at 240°C for 2 seconds. The residue content after welding is calculated by the mass change before and after welding. Each solder paste is welded at least 5 times with a weighing accuracy of ±0.001 g. The residue content Δm after welding is calculated using formula (1). The results are averaged. The specific data are shown in Table 6.
[0088] Δm=1000×[0.17m1-(m2-m3)]······(1);
[0089] Formula (1): m1 is the printing mass of solder paste on the copper substrate, g; m2 is the total mass of solder paste and copper substrate before soldering, g; m3 is the total mass of solder paste and copper substrate after soldering, g.
[0090] 2. Surface insulation resistance test
[0091] Surface insulation resistance: The solder pastes of Examples 1-3 and Comparative Examples 1-15 were tested for insulation resistance using a high resistance meter according to the method of "JIS Z 3197: 2021". The test conditions were 85 ° C, 85% RH, the test time was 186 h, and the applied voltage was 100 V. The specific data are shown in Table 6.
[0092] 3. Fatigue resistance test
[0093] First, print each group of solder paste on the PCB board, and then perform reflow soldering. Test the bonding strength of the solder joints. Then send each group of samples into a small rapid temperature change test chamber for thermal cycle testing. The thermal cycle cycle is 1000 times, and the cycle unit is: heating from -40℃ to 125℃ for 15min, keeping at 125℃ for 30min, cooling from 125℃ to -40℃ for 15min, keeping at -40℃ for 30min, and then test the bonding strength of the solder joints after taking them out. The test method for bonding strength is: test the shear strength of the fracture of each group of solder joints.
[0094] 4. Electromigration
[0095] The evaluation is carried out in accordance with item 6.12 of GB / T 35474-2015 "Flux for high-quality internal interconnection of electronic assembly". The evaluation criteria are as follows: take out the test piece and use a 10x to 30x magnifying glass to observe whether the comb-like pattern has dendrites or corrosion. The dendrite growth rate of the test piece should not exceed 25% of the wire gap (dendrite growth rate = dendrite growth length / wire gap × 100%). If it exceeds 25%, it is unqualified.
[0096] Table 6 Test results of each group of samples
[0097]
[0098] Result analysis:
[0099] According to the results, the thixotropic agent provided by the present invention has extremely high stability, can prevent ion migration, has high insulation impedance, does not produce corrosive electromigration, reduces dendrite growth, and thus reduces the risk of short circuits in fine-pitch solder joints;
[0100] The activator provided by the present invention can achieve decomposition after high-temperature welding. After welding, it has low acid residue, low risk of ion migration, high insulation impedance, no corrosive electromigration, reduced dendrite growth, and thus reduced the risk of short circuit in fine-pitch solder joints.
[0101] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A highly reliable anti-dendrite solder paste, characterized in that: The solder paste comprises the following components by mass: 85-88 parts of solder alloy powder and 12-15 parts of flux; The solder alloy powder is SnAgCuBi alloy powder; The soldering flux is composed of the following components in percentage by mass: Compound rosin 27-35%; Compound resin 13-15%; Activator 4-8%; Thixotropic agent 2-3%; Antioxidants 0.7-1%; Solvent residue; The compound rosin is composed of water-white hydrogenated rosin, acrylic rosin and light-colored rosin; The activator is composed of myristic acid, 4-hydroxyphenylpyruvic acid and triethanolamine tris(dihydrogen phosphite) sodium salt; The thixotropic agent consists of polyamide-modified hydrogenated castor oil, ethylenebismyristic acid amide and polyethylene wax.
2. The anti-dendrite high-reliability solder paste according to claim 1, characterized in that: The solder alloy powder is composed of the following components in percentage by mass: Ag 2.5-3.5%; Cu 0.5-1%; Bi 0.05-0.1%; The balance is Sn and inevitable impurities.
3. The anti-dendrite high-reliability solder paste according to claim 1, characterized in that: The mass ratio of water-white hydrogenated rosin, acrylic rosin and light-colored rosin in the compound rosin is (2-3):1:(1-2).
4. The anti-dendrite high-reliability solder paste according to claim 1, characterized in that: The mass ratio of myristic acid, 4-hydroxyphenylpyruvic acid and triethanolamine tris(dihydrogen phosphite) sodium salt in the activator is 4:(0.3-0.5):(1.4-2.1).
5. The anti-dendrite high-reliability solder paste according to claim 1, characterized in that: The mass ratio of polyamide-modified hydrogenated castor oil, ethylenebismyristamide and polyethylene wax in the thixotropic agent is 1:(1.1-1.4):(1.8-2.2).
6. The anti-dendrite high-reliability solder paste according to claim 1, characterized in that: The antioxidant is at least one of methylbenzotriazole, 2-methylimidazole and benzimidazole.
7. The anti-dendrite high-reliability solder paste according to claim 1, characterized in that: The compound resin is a compound of at least two of polyethylene, polypropylene and polycarbonate.
8. The anti-dendrite high-reliability solder paste according to claim 1, characterized in that: The solvent is a mixture of triethylene glycol butyl ether and diethylene glycol monooctyl ether in a mass ratio of (2-3):
1.
9. The method for preparing the anti-dendrite high-reliability solder paste according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh each component according to the formula and set aside; (2) Add the solvent into the container, heat to 110-130°C and keep warm, add the compound rosin, stir until the compound rosin is completely dissolved, continue to add the compound resin, stir and mix evenly, and obtain mixture A; (3) Lowering the temperature of mixture A to 70-80°C and then keeping it warm, adding a thixotropic agent, an activator and an antioxidant, and stirring for 20-30 minutes to obtain a soldering flux; (4) Add the flux obtained in step (3) and the solder alloy powder into a solder paste mixer, mix and stir for 30-60 minutes to obtain the anti-dendrite high-reliability solder paste; The particle size of the solder alloy powder is ≤40 μm, and the content of the solder alloy powder with a particle size of 20-38 μm is 90 wt% or more.
10. The method for preparing the anti-dendrite high-reliability solder paste according to claim 9, characterized in that: The stirring speed in step (3) is 300-500 r / min; the mixing and stirring speed in step (4) is 30 r / min.
Citation Information
Patent Citations
Low-temperature soldering flux component and preparation method thereof
CN117047341A
Low-silver alternative to standard sac alloys for high reliability applications
US20190134758A1